Exposure to e-cigarette advertising and provaping websites, and the social acceptability of their use among nicotine users - Inti Barrientos-Gutierrez; Katia Gallegos-Carrillo; Lizeth Cruz-Jimenez; Rosibel Rodriguez-Bolaños; Edna Arillo-Santillán; James F. Thrasher (Pan American Health Organization, 2022)
Objectives. To evaluate the prevalence of exposure to Internet communications on and advertising of electronic cigarettes (e-cigarettes) and their association with perceptions of the social acceptability of e-cigarettes in Mexico. Methods. Data were analyzed from eight surveys (2018-2021) of an online sample of Mexican adult (> 18 years) smokers and dual users (of combustible and electronic cigarettes). Self-reported exposure to e-cigarette advertising across various marketing channels was assessed, as well as visits to e-cigarette websites. Logistic regression analysis was used to evaluate the association between perceptions of the social acceptability of e-cigarette use and level of advertising exposure and visits to e-cigarette websites. Results. The Internet and outside e-cigarette stores were where exposure to advertising most occurred, as reported by 47.4% and 46.8% of respondents, respectively. Respondents who noticed e-cigarette advertisements on the Internet (adjusted odds ratio (OR) 1.43, 95% confidence intervals (CI) 1.25, 1.63), outside e-cigarette stores (adjusted OR 1.31, 95% CI 1.14, 1.50), and in temporary outlets (adjusted OR 1.16, 95% CI 1.01, 1.34), and those who visited e-cigarette websites (adjusted OR 1.48, 95% CI 1.25, 1.76) were more likely to perceive e-cigarettes as socially acceptable. Noticing advertisements across more channels was also associated with higher perceived social acceptability of e-cigarette use. Conclusions. Being exposed to e-cigarette marketing, either online or through traditional marketing channels, is associated with perceived social acceptability of e-cigarette use, as is contact with provaping sites. Regulatory options to avoid the proliferation of promotional websites disguised as opinion or user sites need to be considered.